CSP files - Roscoe, T; Nguyen, L (2011)
On this page, you can download CSP files that illustrate the technique we discussed in the paper entitled \"Model checking cryptographic protocols subject to combinatorial attack\" of A.W. Roscoe, Toby Smyth and Long Nguyen at the Oxford University Department of Computer Science.